2017
DOI: 10.3390/ijerph14101253
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of PM10 and the Incidence of Lung Cancer in Nanchang, China

Abstract: Air pollution and lung cancer are closely related. In 2013, the World Health Organization listed outdoor air pollution as carcinogenic and regarded it as the most widespread carcinogen that humans are currently exposed to. Here, grey correlation and data envelopment analysis methods are used to determine the pollution factors causing lung cancer among residents in Nanchang, China, and identify population segments which are more susceptible to air pollution. This study shows that particulate matter with particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Probably due to the majority of Chinese women had to take on the responsibilities of cooking, therefore more vulnerable exposed to cooking oil fume, which is likely to be a risk factor for lung cancer . Especially another study also found that women are more susceptible to lung cancer caused by air pollution . However, due to limited historical data collection of air pollution in Shanghai, there still needs further research to explore the association between air pollution and the incidence of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Probably due to the majority of Chinese women had to take on the responsibilities of cooking, therefore more vulnerable exposed to cooking oil fume, which is likely to be a risk factor for lung cancer . Especially another study also found that women are more susceptible to lung cancer caused by air pollution . However, due to limited historical data collection of air pollution in Shanghai, there still needs further research to explore the association between air pollution and the incidence of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to rapid urbanization and climate change in recent years, severe and sustained air pollution has also led to an increase in morbidity and mortality [18][19][20]. In the past, research on the adverse health effects of air pollution has focused on the relationship between air pollution and chronic noncommunicable diseases [21,22]. However, recent studies have shown that air pollution may affect the incidence of infectious diseases [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…GRA has been described previously in our study in which GRA was used to identify which population segment was more susceptible to air pollution which caused lung cancer in Nanchang, China, and which air pollutant was the main cause of lung cancer [37]. Our previous study result shown that PM 10 is the main cause of lung cancer.…”
Section: Grey Correlation Eory Grey Relation Analysis (Gra)mentioning
confidence: 81%